Five Proteins of Laodelphax striatellus Are Potentially Involved in the Interactions between Rice Stripe Virus and Vector - Li, Shuo (Public Library of Science, 2011)
Rice stripe virus (RSV) is the type member of the genus Tenuivirus, which relies on the small brown planthopper (Laodelphax striatellus Fallén) for its transmission in a persistent, circulative-propagative manner. To be transmitted, virus must cross the midgut and salivary glands epithelial barriers in a transcytosis mechanism where vector receptors interact with virions, and as propagative virus, RSV need utilize host components to complete viral propagation in vector cells. At present, these mechanisms remain unknown. In this paper, we screened L. striatellus proteins, separated by two-dimensional electrophoresis (2-DE), as potential RSV binding molecules using a virus overlay assay of protein blots. The results, five L. striatellus proteins that bound to purified RSV particles in vitro were resolved and identified using mass spectrometry. The virus-binding capacities of five proteins were further elucidated in yeast two-hybrid screen (YTHS) and virus-binding experiments of expressed proteins. Among five proteins, the receptor for activated protein kinase C (RACK) and glyceraldehyde-3-phosphate dehydrogenase (GAPDH3) did not interact with RSV nucleocapsid protein (NCP) in YTHS and in far-Western blot, and three ribosomal proteins (RPL5, RPL7a and RPL8) had specific interactions with RSV. In dot immunobinding assay (DIBA), all five proteins were able to bind to RSV particles. The five proteins' potential contributions to the interactions between RSV and L. striatellus were discussed. We proposed that RACK and GAPDH3 might be involved in the epithelial transcytosis of virus particles, and three ribosomal proteins probably played potential crucial roles in the infection and propagation of RSV in vector cells.